Germline BRCA1/2 mutations and severe haematological toxicities in patients with breast cancer treated with neoadjuvant chemotherapy. (March 2021) - Furlanetto, Jenny; Möbus, Volker; Schneeweiss, Andreas; Rhiem, Kerstin; Tesch, Hans; Blohmer, Jens-Uwe; Lübbe, Kristina; Untch, Michael; Salat, Christoph; Huober, Jens; Klare, Peter; Schmutzler, Rita; et al.
Abstract: Background: BRCA1 and BRCA2 play a central role in DNA repair. Therefore, patients harbouring germline (g) BRCA1/2 mutations ( m) treated with chemotherapy might be at higher risk of haematological toxicities. Methods: Patients from German Breast Group (GBG) and Arbeitsgemeinschaft Gynäkologische Onkologie-breast group studies with early triple-negative breast cancer (TNBC) and known g BRCA1/2 m status treated with anthracycline-taxane-based neoadjuvant chemotherapy were analysed. Primary objective was the rate of neutropenia grade (G)III–IV in cycle 1 (C1). Secondary objectives included effects on overall and other haematological toxicities GIII-IV in C1, cumulative haematological toxicity across all cycles, relative total dose intensity, and granulocyte-colony stimulating factor prophylaxis. Haematological toxicities under taxanes, carboplatin, and cyclophosphamide were explored. Results: Two hundred nine of 1171 (17.8%) evaluated patients had g BRCA1/2m . In C1, 37.4% g BRCA1/2m versus 35.7% wild-type patients had neutropenia GIII-IV (P = 0.683). For C1, g BRCA1/2m predicted neither for neutropenia GIII-IV (odds ratio [OR]: 1.26, 95% confidence intervals [CI]: 0.87–1.82, P = 0.226) nor for other haematological toxicities GIII-IV (OR: 0.91, 95% CI: 0.64–1.31, P = 0.625) in multivariable regression models. Analyses of cumulative toxicities across all cycles yielded similar results except thrombocytopaenia GIII-IV, which was increased in g BRCA1 m patients. In patients treated with taxanes, the rate of haematological toxicities GIII-IV was higher in g BRCA1/2 m compared with wild-type (59.5% versus 43.1%; p < 0.001). No difference was seen under cyclophosphamide or platinum-containing chemotherapies. Conclusions: g BRCA1/2 m was not associated with higher risk of overall severe haematological toxicities in the first cycle or cumulatively across all cycles under standard chemotherapy for TNBC. Under taxane, patients with g BRCA1/2m might have a higher risk of haematological toxicities GIII-IV, requiring further research. Highlights: g BRCA1/2 mutation did not increase overall toxicities after the first or all cycles. g BRCA1/2 mutation did not affect severe haematological toxicities. Difference in febrile neutropenia according to g BRCA status was negligible. Severe thrombocytopaenia was increased in the subgroup of g BRCA1 -mutant patients. g BRCA1/2 mutation status did not impact the total dose intensity of chemotherapy.